Pesantren di Era Revolusi Industri 4.0: Implementasi Sistem Informasi Berbasis Web pada Pondok Pesantren - Abdul Chalim Ibnu Umar; Shofia Rizka Julianti (Jurnal Pendidikan dan Pengabdian Masyarakat, 2026)
Islamic boarding schools face a number of fundamental problems, such as weak institutional governance, limited quality and quantity of human resources, low mastery of Information and Communication Technology, an underdeveloped research culture, limited infrastructure, and suboptimal data quality. The implementation of a web-based information system in Islamic boarding schools is necessary to maintain a balance between technological modernization and the preservation of Islamic values. The method for implementing community service is designed with a participatory and applicative approach. The activity stages are arranged into three main parts, namely planning, implementation, and evaluation. The findings indicate that the implementation of a web-based system in Islamic boarding schools is considered highly effective because it not only improves the technical aspects of services but also transforms work mechanisms to be more systematic, fast, and easily accessible. Web-based information systems in Islamic boarding schools can be seen as a strategic necessity in facing the challenges of the Industrial Revolution 4.0, but their impact will be optimal only if accompanied by strengthening organizational capacity and sustainable management. Islamic boarding schools need to formulate a more targeted digital transformation policy so that the development of web-based information systems in Islamic boarding schools does not stop at the creation stage, but continues to active, integrated, and sustainable use.